Suspected Sugammadex Hypersensitivity following Repeated Administration in the Setting of Multiple Flap Takebacks in a Brief Timespan. (23rd August 2021) - Zolper, Elizabeth G.; Kim, Alan H.; Kim, Kevin G.; Dekker, Paige K.; Bekeny, Jenna C.; Song, David H.; Fan, Kenneth L.
Abstract : Sugammadex hypersensitivity is an uncommon event that typically occurs at higher doses. We report a case of suspected sugammadex hypersensitivity in a patient who developed hypoxia and bronchospasm following three administrations of the standard 2 mg/kg doses of sugammadex within 26 hours due to flap takebacks. Hypersensitivity to sugammadex was not initially suspected given that the patient had previous exposures. Diagnoses of pneumothorax, hemothorax, mucus plug, and tracheal tube malposition were immediately ruled out. Furthermore, the onset of hypoxia with sudden loss of tidal volume, development of high peak airway pressures, and temporal correlation with sugammadex administration all supported bronchospasm secondary to a hypersensitivity reaction. Sugammadex is a useful agent for neuromuscular blockade reversal; however, it is critical to carefully examine all adverse reactions. This case report highlights the importance of considering hypersensitivity reactions in the setting of repeat sugammadex administrations in a limited timeframe, such as in free flap reconstruction requiring multiple takebacks to the operating room in the setting of flap compromise.